2021
DOI: 10.1038/s43016-020-00210-8
|View full text |Cite
|
Sign up to set email alerts
|

Crop cover is more important than rotational diversity for soil multifunctionality and cereal yields in European cropping systems

Abstract: In natural ecosystems, positive effects of plant diversity on ecosystem functioning have been widely observed, yet whether this is true in cropping systems remains unclear. Here we assessed the impact of crop diversification on soil microbial diversity, soil multifunctionality (SMF), and crop yields in 155 cereal fields across a 3,000 km North-South European gradient. Overall, crop diversity showed a relatively minor effect on soil microbial diversity, SMF and yields. In contrast, the proportion of time with c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
95
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 160 publications
(99 citation statements)
references
References 66 publications
3
95
0
1
Order By: Relevance
“…A recent study highlights a positive effect of cover crop diversity on bacterial microbiota evenness. However, Garland et al (2021) showed this effect to be negligible when considering environmental factors. The low impact of cover crop diversity on microbial biodiversity might be attributed to the occurrence of sampling when one crop is implemented in the field.…”
Section: Impact Of Soil Cover On Soil Microbiotamentioning
confidence: 96%
See 1 more Smart Citation
“…A recent study highlights a positive effect of cover crop diversity on bacterial microbiota evenness. However, Garland et al (2021) showed this effect to be negligible when considering environmental factors. The low impact of cover crop diversity on microbial biodiversity might be attributed to the occurrence of sampling when one crop is implemented in the field.…”
Section: Impact Of Soil Cover On Soil Microbiotamentioning
confidence: 96%
“…Beyond the beneficial traits harbored by cover crop-recruited soil microbiota, Romdhane et al (2019) considered how to select an appropriate way to terminate cover crops. According to Alahmad et al (2019), Cloutier et al (2020), andGarland et al (2021), farmers could eventually resort to cover crop diversity and duration to induce shifts in both bacterial and fungal microbiomes in order to reduce fertilization needs while maintaining yields. There is still much work to be done with regard to the low number of studies investigating the impact of cover crops from a metagenomic perspective.…”
Section: Impact Of Soil Cover On Soil Microbiotamentioning
confidence: 99%
“…According to its history and ecological characteristics the species could be an ideal catch crop (or flower strip crop) in the ecological focus areas of the EU's greening programs (Pe'er et al 2017), allowing for an increased green cover diversification. According to Garland et al (2021), a diverse portfolio of such catch crops and cover crops can also significantly contribute to the conservation of soil multifunctionality. In Switzerland, for example, S. annua is already available as a component of seed mixtures to promote biodiversity in agro-ecosystems (Ramseier et al 2016;Ganser et al 2019).…”
Section: Prospects For Revivalmentioning
confidence: 99%
“…We further aimed at identifying the best environmental (climatic, edaphic and geomorphological) predictors of the overall archaeal diversity and determining the factors governing their community assembly processes in soil. To this end, we sampled arable soils along a 3 000 km European gradient, spanning from northern Sweden to southern Spain [29]. Such continental surveys focusing on archaea are rare [30] and represent a signi cant opportunity to gain insight into their ecology by capturing broad environmental gradients.…”
Section: Introductionmentioning
confidence: 99%
“…Such continental surveys focusing on archaea are rare [30] and represent a signi cant opportunity to gain insight into their ecology by capturing broad environmental gradients. By only including arable elds under cereal cultivation and conventional tillage [29], management effects were minimized. For the AOA, machine learning in terms of random forest modeling [31] was used to determine the environmental drivers of Nitrososphaeria diversity and AOA abundances.…”
Section: Introductionmentioning
confidence: 99%